A study on information needs of dairy farmers in hill region of Uttarakhand - Adhikari, Babita; Chauhan, Amardeep; Bhardwaj, Neelam; Kameswari, V LV (Indian Journal of Dairy Science, 2020)
Dairy farming is an indispensable economic activity in the rural hill region of Uttarakhand which is closely intervened with farming systems. Despite its relative importance contradicting facts appear in case of milk production and milk productivity in hill region Uttarakhand. The milk production of the state is 1.656 MT which contributes only 1.15 percent to dairy industry of the entire nation. There is huge information gap which is major problem in dairy farming. Moreover, information is said to be appropriate when are based upon local situation meeting their basic dairy needs. Against this backdrop, the present study was conducted to assess the information needs of dairy farmers. The study revealed that majority of the respondents (75.83%) had moderate information needs on breeds, majority of the respondents (81.7%) had moderate information needs regarding fodder production. There were moderate information needs regarding health care practices among majority of the respondents and majority of the respondents (66.67%) had moderate information needs regarding input supplies and record keeping. All the respondents ‘not needed’ the information regarding preparation of milk products of dairy animals. Majority of the respondents (60.83%) had moderate overall information needs. It was further indicated that land holding, herd size, material possession, achievement motivation and scientific orientation were negatively and highly significantly correlated with information needs of dairy farmers.